People and protected areas : natural resource harvesting as an approach to support rural communities surrounding Majete Wildlife Reserve, Southern Malawi : a case study - Gordon, Claire Nicola (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScConsEcol)--Stellenbosch University, 2017.